A practical guide to global health service - O'Neil, Edward; American Medical Association (Chicago : American Medical Association, 2006)
"A health providers guide to the practical aspects of serving internationally, including data on more then 300 organizations that send health providers overseas"--Provided by publisher.
Overcoming obstacles: cultural and practical guidelines -- Travel, health, and safety guidelines -- The Omni Med database of international health service opportunities -- Cross-referencing guide to the database -- Other relevant organizations.
Includes bibliographical references (p. [397]-402).
Keywords: Medical assistance, American; Public health -- International cooperation; Voluntary health agencies -- Directories; Volunteer workers in medical care; World health; World Health -- Directory; International Cooperation -- Directory; Organizations -- Directory; Voluntary Workers